Penurunan Tingkat Kecemasan Anak Akibat Hospitalisasi dengan Penerapan Terapi Bermain - Heri Saputro; Intan Fazrin (JKI (Jurnal Konseling Indonesia), 2017)
Children who are sick and hospitalized have an impact, both physically and psychologically, such as anxiety, feeling alien to the new environment, dealing with unknown individuals, lifestyle changes and having to accept painful medical or medical treatment. The purpose of this study was to determine the decrease in anxiety of children treated in hospital with the provision of play therapy. This research is a pre experimental research using One Group Pretest-Posttest Design approach in pre-school age children. The study was aimed at hospitalized children who experienced anxiety during hospitalization, then 3-day intervention (play therapy), then re-examined anxiety levels in children, anxiety measurements using a modified Spence Children's Anxiety Scale Parent Report And has tested the validity. The results showed a decrease in child's anxiety after being given a play therapy intervention with a p value of 0.002.